Answer:
See the proof below.
Step-by-step explanation:
For this case we need to proof that: Let [tex] X_1, X_2, ...X_n \in R[/tex] be independent random variables with a common CDF [tex] F_0[/tex]. Let [tex] F_n[/tex] be their ECDF and let F any CDF. If [tex] F \neq F_n[/tex] then [tex] L(F) <L(F_n)[/tex]
Proof
Let [tex] z_a<z_2<....<z_m[/tex] different values in the set {[tex] X_1,X_2,...,X_n}[/tex]} and we can assume that [tex] n_j \geq 1[/tex] represent the number of [tex] X_i[/tex] that are equal to [tex]z_j[/tex].
We can define [tex] p_j = F(z_j) +F(z_j-)[/tex] and assuming the probability [tex] \hat p_j = \frac{n_j}{n}[/tex].
For the case when [tex] p_j =0[/tex] for any [tex] j=1,....,m[/tex] then we have that the [tex]L(F) =0< L(F_n)[/tex]
And for the case when all [tex] p_j >0[/tex] and for at least one [tex]p_j \neq \hat p_j[/tex] we know that [tex] log(x) \leq x-1[/tex] for all the possible values [tex]x>0[/tex]. So then we can define the following ratio like this:
[tex] log (\frac{L(F)}{L(F_n)}) = \sum_{j=1}^m n_j log (\frac{p_j}{\hat p_j})[/tex]
[tex] log (\frac{L(F)}{L(F_n)}) = n \sum_{j=1}^m \hat p_j log(\frac{p_j}{\hat p_j})[/tex]
[tex] log (\frac{L(F)}{L(F_n)}) < n\sum_{j=1}^m \hat p_j (\frac{p_j}{\hat p_j} -1)[/tex]
So then we have that:
[tex] log (\frac{L(F)}{L(F_n)}) \leq 0[/tex]
And the log for a number is 0 or negative when the number is between 0 and 1, so then on this case we can ensure that [tex] L(F) \leq L(F_n)[/tex]
And with that we complete the proof.